CIC2: a radiation tolerant 65 nm data aggregation ASIC for the future CMS tracker. (1st May 2022) - Viret, S.; Bergamin, G.; Caponetto, L.; Caratelli, A.; Ceresa, D.; Galbit, G.; Jain, S.; Kloukinas, K.; Nodari, B.; Scarfi, S.
Abstract: The Concentrator Integrated Circuit (CIC) ASIC is a front-end chip for both Pixel-Strip (PS) and Strip-Strip (2S) modules of the future Phase-II CMS Outer Tracker upgrade at the High-Luminosity LHC (HL-LHC). This data aggregator, designed in 65 nm CMOS technology, will be a key element of the tracker front-end chain. A first prototype, CIC1, was tested successfully in early 2019 and was followed by the development of a final radiation tolerant version of the chip: the CIC2. CIC2 design, implementation, and complete test results, are presented.